PENERAPAN DESAIN KELAS MODEL ‘’U’’ TERHADAP MOTIVASI BELAJAR MATEMATIKA DI UPT SD NEGERI 73 GRESIK KELAS IV - Muhammad Bayu Baharudin; Nataria Wahyuning Subayani; Arya Setya Nugraha (Universitas Muhammadiyah Gresik, 2022)
Learning motivation is something that can change the behavior of students for the better with the aim of obtaining maximum learning outcomes. Motivation is needed in ongoing learning activities, because motivation acts as a driving force in oneself that supports learning activities. Learning motivation can be said as an encouragement that makes a person take certain actions in order to achieve a goal, either internally or externally in the hope of obtaining complete learning outcomes which learning outcomes obtained above the KKM. However, there are still students who have low learning motivation. The arrangement of the